Efficient synthesis of optically active herbicide (S)-metolachlor via reductive ring opening of 2-methoxymethylaziridine - Nalla, Viswanadh; Mujahid, Mohammad; Sasikumar, Murugesan; Mujumdar, Prashant; Muthukrishnan, Murugan (Arkivoc, 2023)
An efficient synthesis of a well known chiral herbicide, (S)-metolachlor has been described using 2methoxymethylaziridine ring formation and reductive ring opening as key steps using commercially available (R)-epichlorohydrin. The present protocol delivers the required enantiomer of metolachlor in overall yield of 50.8% and high enantiopurity (>99%).
Keywords: Aziridine; Epoxide; Epoxide ring opening; herbicide synthesis; Metolachlor